Implementation of Implantation-Stagger Measuring Unit using Image Processing - Angela Infanta Ramesh; Ashish Dinesh Singh; Battina Babykutty; Dheeraj Kallakuri (International Journal of Engineering and Management Research, 2021)
The electrical traction system of railways is a combination of physical upright structures and OCL(Overhead Contact Lines). The horizontal distance from the center of the track to the OHE mast called implantation, horizontal displacement of overhead contact wire with respect to the center of the railway track called stagger, and the perpendicular height of overhead contact wire from the ground are periodically checked by a lineman in order to ensure a safe distance from the railway track. In this paper, we have put forth an idea of building a distance measuring device to measure the implantation and stagger without touching the objects using Open CV on raspberry pi with a camera module which will be placed at the center of the track. The system will be having two features. To measure the distance of the nearest poles, the camera has to be placed facing the mast perpendicular to a circle of diameter appropriate which is placed on the pole for measurement purposes. And to measure the stagger, the camera has to be placed facing the overhead wire from the center of the track.